Antimicrobials used for surgical prophylaxis by equine veterinary practitioners in Australia. (10th July 2017) - Hardefeldt, L. Y.; Browning, G. F.; Thursky, K.; Gilkerson, J. R.; Billman‐Jacobe, H.; Stevenson, M. A.; Bailey, K. E.
Summary: Background: Antimicrobials are widely used in Australian veterinary practices, but no investigation into the classes of antimicrobials used, or the appropriateness of use in horses, has been conducted. Objectives: The aim of the study was to describe antimicrobial use for surgical prophylaxis in equine practice in Australia. Study design: Cross‐sectional questionnaire survey. Methods: An online questionnaire was used to document antimicrobial usage patterns. Information solicited in the questionnaire included demographic details of the respondents, the frequency with which antimicrobials were used for specific surgical conditions (including the dose, timing and duration of therapy) and practice antimicrobial use policies and sources of information about antimicrobials and their uses. Results: A total of 337 members of the Australian veterinary profession completed the survey. Generally, the choice of antimicrobial was appropriate for the specified equine surgical condition, but the dose and duration of therapy varied greatly. While there was poor optimal compliance with British Equine Veterinary Association guidelines in all scenarios (range 1–15%), except removal of a nonulcerated dermal mass (42%), suboptimal compliance (compliant antimicrobial drug selection but inappropriate timing, dose or duration of therapy) was moderate for all scenarios (range 48–68%), except for an uninfected contaminated wound over the thorax, where both optimal and suboptimal compliance was very poor (1%). Veterinarians practicing at a university hospital had higher odds of compliance than general practice veterinarians (Odds ratio 3.2, 95% CI, 1.1–8.9, P = 0.03). Main limitations: Many survey responses were collected at conferences which may introduce selection bias, as veterinarians attending conferences may be more likely to have been exposed to contemporary antimicrobial prescribing recommendations. Conclusions: Antimicrobial use guidelines need to be developed and promoted to improve the responsible use of antimicrobials in equine practice in Australia. An emphasis should be placed on antimicrobial therapy for wounds and appropriate dosing for procaine penicillin.